The diagnosis and management of patients with idiopathic osteolysis - Hofstaetter Jochen G; Maurer Kathrin; Biedermann Rainer; Scholl-Buergi Sabine; Al Kaissi Ali; Klaushofer Klaus; Grill Franz (BMC, 2011)
Abstract Idiopathic osteolysis or disappearing bone disease is a condition characterized by the spontaneous onset of rapid destruction and resorption of a single bone or multiple bones. Disappearing bone disorder is a disease of several diagnostic types. We are presenting three patients with osteolysis who have different underlying pathological features. Detailed phenotypic assessment, radiologic and CT scanning, and histological and genetic testing were the baseline diagnostic tools utilized for diagnosis of each osteolysis syndrome. The first patient was found to have Gorham-Stout syndrome (non-heritable). The complete destruction of pelvic bones associated with aggressive upward extension to adjacent bones (vertebral column and skull base) was notable and skeletal angiomatosis was detected. The second patient showed severe and aggressive non-hereditary multicentric osteolysis with bilateral destruction of the hip bones and the tarsal bones as well as a congenital unilateral solitary kidney and nephropathy. The third patient was phenotypically and genotypically compatible with Winchester syndrome resulting in multicentric osteolysis (autosomal recessive). Proven mutation of the (MMP2-Gen) was detected in this third patient that was associated with 3MCC deficiency (3-Methylcrontonyl CoA Carboxylase deficiency). The correct diagnoses in our 3 patients required the exclusion of malignant osteoclastic tumours, inflammatory disorders of bone, vascular disease, and neurogenic arthropathies using history, physical exam, and appropriate testing and imaging. This review demonstrates how to evaluate and treat these complex and difficult patients. Lastly, we described the various management procedures and treatments utilized for these patients.